Proses Anak Angkat Perpektif Peraturan Pemerintah Nomor 54 Tahun 2007 Tentang Pelaksanaan Pengangkatan Anak - Aprilia Nur Khasanah; Habibi al-Amin (Menara Tebuireng, 2023)
This study uses qualitative research. This study uses an empirical legal approach, especially to find out the practice of adoption. Data collection techniques using decision research and field research methods which include observation and interviews. The results of the study show that the practice of adopting children in the Pundong village community does not go through judicial procedures, so that the person who is adopted does not get all the rights of the person who is adopted due to a lack of community knowledge. about laws and regulations Keywords: Child Adoption, Court Determination, PP No. 54 of 2007